Handling and Enforcement of Illegal Fishing Laws in Indonesia Based on Law Number 45 of 2009 Concerning Amendments to Law Number 31 of 2004 Concerning Fisheries - Josept Prayego Matondang; Abdul Hakim; Maya Jannah (Journal of Social Research, 2023)
Illegal fishing practices are national in nature which are still difficult to prevent in Indonesian waters and international glass and have not been able to be eradicated without international cooperation. A number of international agreements and cooperation in the field of international law of the sea and fisheries as well as international criminal have not been able to categorize illegal fishing as an international crime. This article discusses related regulations on illegal fishing according to Indonesian national law and examines the urgency of tackling illegal fishing as a crime that is still always discussed nationally and internationally. This article is a normative legal research with a statutory approach that traces relevant national legal instruments until they are analyzed by descriptive methods. The results of the study show that illegal fishing has been regulated firmly and well in Indonesian laws and regulations. Illegal fishing is a crime that has characteristics across national borders. In terms of the implementation of Indonesia's national law, until now there seems to be no coordination between the central government and local governments in establishing a mechanism related to prevention efforts.